2021
DOI: 10.2459/jcm.0000000000001127
|View full text |Cite
|
Sign up to set email alerts
|

Results of paclitaxel-drug-coated balloons (Pantera Lux) for coronary in-stent restenosis: Italian experience from REGistry of Paclitaxel Eluting Balloon in ISR study

Abstract: Aims Drug-eluting stent (DES) implantation is an effective treatment of in-stent restenosis (ISR). However, literature data indicate that drug-coated balloons (DCBs) may be a valid alternative, particularly for recurrent ISR. We sought to evaluate clinical results on the long-term efficacy of a new DCB for ISR treatment. Methods One hundred and ninety-nine patients were treated with paclitaxel drug-coated balloons (Pantera Lux, Biotronik, Switzerland) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(56 reference statements)
1
3
0
Order By: Relevance
“…An interim analysis of 12-month follow-up showed a good performance of this device, along with an adequate safety profile 33 . The Italian REGistry of Paclitaxel Eluting Balloon in ISR (REGPEB study) included patients treated with paclitaxel DCBs (Pantera Lux, Biotronik) 34 . Even the results of this study confirmed the efficacy and safety of DCBs treatment, showing excellent performances up to 5 years after the procedure.…”
Section: Managementsupporting
confidence: 58%
See 2 more Smart Citations
“…An interim analysis of 12-month follow-up showed a good performance of this device, along with an adequate safety profile 33 . The Italian REGistry of Paclitaxel Eluting Balloon in ISR (REGPEB study) included patients treated with paclitaxel DCBs (Pantera Lux, Biotronik) 34 . Even the results of this study confirmed the efficacy and safety of DCBs treatment, showing excellent performances up to 5 years after the procedure.…”
Section: Managementsupporting
confidence: 58%
“…Even the results of this study confirmed the efficacy and safety of DCBs treatment, showing excellent performances up to 5 years after the procedure. Drug-coated balloons have several advantages as compared with DES such as avoiding multiple strut layers, shorter dual antiplatelet therapy and subsequently fewer bleeding complications, and are theoretically repeatable several times 34 …”
Section: Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Refractory ISR represents a major problem in CCS patients and its optimal management is still a matter of debate. Drug-coated balloons are safe and effective 1,2 ; however, in the setting of calcified neo-atherosclerosis, plaque-modifying tools (such as IVL and rotational atherectomy) can be needed. Sometimes, therapeutic combinations are required 3 .…”
Section: Discussionmentioning
confidence: 99%